Being Muslim the Bosnian way : identity and community in a central Bosnian village - Bringa, Tone, 1960- (Princeton studies in Muslim politics., 1995)
"I have been able to follow a Bosnian community over a period of six years, during which it has undergone dramatic changes and events. In the late eighties people were working hard against ... economic crisis ... In 1990 they were full of optimism about the future ... In January 1993 it was a village in fear surrounded by war on all sides ... In April 1993 the village was attacked by Croat forces. In October 1993 none of the four hundred Muslims in the village remained. They had either fled, been placed in detention camps, or been killed." Thus begins Tone Bringa's moving ethnographic account of Bosnian Muslims' lives in a rural village located near Sarajevo. Although they represent a majority of the population in the Republic of Bosnia and Herzegovina, Bosnian Muslims are still members of a minority culture in the region that was once Yugoslavia. The question of ethno-national identity has become paramount in this society, and the author focuses on religion as the defining characteristic of identity. Bringa pays particular attention to the roles that women play in defining Muslim identities, and she examines the importance of the household as a Muslim identity sphere. In so doing, she illuminates larger issues of what constitutes "nationality." This is a gripping and heartfelt account of a community that has been torn apart by ethnopolitical conflict. It will attract readers of all backgrounds who want to learn more about one of the most intractable wars of the late twentieth century and the people who have been so tragically affected.